All-solid-state battery and end-point voltage detection method of all-solid-state battery

By using positive and negative electrode active materials with different average working potentials in an all-solid battery, the end voltage is detected using the flat part of the discharge curve, which solves the problem of difficult to detect the drop in the battery voltage and achieves stable and efficient use of the battery.

CN113937348BActive Publication Date: 2025-01-03TAIYO YUDEN KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110711459.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-29
Filing Date
2021-06-25
Publication Date
2025-01-03
Estimated Expiration
2041-06-25

AI Technical Summary

Technical Problem

In all-solid batteries, when the battery residual amount decreases, the voltage drop of the single cell becomes difficult to detect, making it difficult to accurately determine the end voltage, which in turn affects the charging and service life of the battery.

Method used

An oxide-based solid electrolyte layer containing positive and negative electrode active substances with different average working potentials is used to determine the end voltage by detecting the flat part in the discharge curve to ensure that the battery starts charging before the single cell voltage does not decrease.

Benefits of technology

It realizes easy endpoint detection in all solid batteries, extends the service life of the battery, and ensures the stability of the single cell voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113937348B_ABST
    Figure CN113937348B_ABST
Patent Text Reader

Abstract

The present invention provides an all-solid-state battery and an endpoint voltage detection method for an all-solid-state battery that are easy to detect an endpoint. The all-solid-state battery is characterized in that it includes: an oxide solid electrolyte layer; a positive electrode layer formed on the first main surface of the oxide solid electrolyte layer, which contains a positive electrode active material; and a negative electrode layer formed on the second main surface of the oxide solid electrolyte layer, which contains a negative electrode active material, and at least one of the positive electrode active material of the positive electrode layer and the negative electrode active material of the negative electrode layer contains an average working potential vsLi / Li + A first active material and a second active material that are different from each other.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an all-solid battery and an endpoint voltage detection method of the all-solid battery. Background Art

[0002] In recent years, secondary batteries have been used in various fields. Secondary batteries using electrolytes have problems such as electrolyte leakage. Therefore, all-solid batteries with solid electrolytes and other components also made of solids have been developed.

[0003] Solid electrolytes have a wider potential window (wider voltage stability) than electrolytes. There are also many solid electrolytes that can be used as 5V-class positive electrode active materials. For example, LiCoPO4 (for example, see Patent Document 1) and Li2CoP2O7 (for example, see Patent Document 2) are solid electrolytes that can be used at about 5V vs Li / Li + By using these active materials, there is an advantage that the cell voltage can be increased, and it is expected to replace button batteries that operate at 3V or more.

[0004] Oxide-based solid electrolytes that exhibit high ion conductivity by sintering have advantages over electrolytes and other solid electrolytes in that they have a wide potential window and are relatively stable in the atmosphere. For example, an all-solid-state battery obtained by co-firing an oxide-based solid electrolyte and a negative electrode active material is disclosed (for example, see Patent Document 3).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2007-005279

[0008] Patent Document 2: Japanese Patent Application Publication No. 2017-157394

[0009] Patent Document 3: International Publication No. 2014 / 038311 Summary of the invention

[0010] Technical problem to be solved by the invention

[0011] In order to drive devices such as IC (Integrated Circuit), it is required to control the voltage of a single cell of an all-solid-state battery so that it does not drop below 1.8V. Therefore, in many all-solid-state batteries, various methods are adopted, such as setting an end voltage (lower limit voltage), charging if the monitored single cell voltage drops to the end voltage, etc. The discharge curve of a general battery changes to a steeper slope relative to the slope of the voltage drop in the potential flat part at the end of the discharge when the battery remaining amount decreases. The voltage drop in a short period of time is the main reason why it is difficult to detect the end point.

[0012] The present invention is made in view of the above-mentioned technical problems, and its purpose is to provide an all-solid-state battery and an endpoint voltage detection method of the all-solid-state battery that are easy to detect the endpoint.

[0013] Means for solving technical problems

[0014] The all-solid-state battery of the present invention is characterized in that it comprises: an oxide solid electrolyte layer; a positive electrode layer formed on a first main surface of the oxide solid electrolyte layer, which contains a positive electrode active material; and a negative electrode layer formed on a second main surface of the oxide solid electrolyte layer, which contains a negative electrode active material, and at least one of the positive electrode active material of the positive electrode layer and the negative electrode active material of the negative electrode layer contains an average working potential vs Li / Li + A first active material and a second active material that are different from each other.

[0015] In the above-mentioned all-solid-state battery, the positive electrode layer may have an average working potential vs Li / Li + A first positive electrode active material and a second positive electrode active material different from each other, wherein the average working potential of the first positive electrode active material vs Li / Li + Average working potential of the second positive electrode active material vs Li / Li + The difference is between 0.2V and 1.5V.

[0016] In the above-mentioned all-solid-state battery, the first positive electrode active material may be LiCoPO4, and the second positive electrode active material may be Li6Co5(P2O7)4.

[0017] In the above-mentioned all-solid-state battery, the second positive electrode active material may have an average crystal particle size of 0.5 μm or more and 50 μm or less.

[0018] In the above-mentioned all-solid-state battery, the average working potential of the first positive electrode active material vs Li / Li + Higher than the average working potential of the second positive electrode active material vs Li / Li +In a cross section of the positive electrode layer, a ratio of an area of ​​the first positive electrode active material to a total area of ​​the first positive electrode active material and the second positive electrode active material is 85% or more.

[0019] In the above-mentioned all-solid-state battery, the positive electrode layer may contain Li2CoP2O7.

[0020] In the above-mentioned all-solid-state battery, the negative electrode layer may have an average working potential vs Li / Li + A first negative electrode active material and a second negative electrode active material different from each other, wherein the average working potential of the first negative electrode active material vs Li / Li + is below 1.9 V, the average working potential of the second negative electrode active material vs Li / Li + Above 2.2V.

[0021] In the above-mentioned all-solid-state battery, the first negative electrode active material may be TiO2, Li 1-2x M x TiOPO4、Li 3x La 2 / 3-x Any one of TiO3, Nb2O5 and Nb-Ti-O based compounds, wherein M is a divalent metal element, and 0≤x≤0.5.

[0022] In the above-mentioned all-solid-state battery, the second negative electrode active material may be a Ti-containing phosphate or TiP2O7 having a NASICON-type crystal structure.

[0023] In the above-mentioned all-solid-state battery, the Ti-containing phosphate may be Li 1+y A y Ti 2-y (PO4)3, wherein A is a trivalent metal element, 0≤y≤0.7.

[0024] In the above-mentioned all-solid-state battery, the second negative electrode active material may have an average crystal particle size of 0.5 μm or more and 50 μm or less.

[0025] The endpoint voltage detection method of the all-solid-state battery of the present invention is characterized in that the all-solid-state battery comprises: an oxide-based solid electrolyte layer; a positive electrode layer formed on a first main surface of the oxide-based solid electrolyte layer, which contains a positive electrode active material; and a negative electrode layer formed on a second main surface of the oxide-based solid electrolyte layer, which contains a negative electrode active material, and at least one of the positive electrode active material of the positive electrode layer and the negative electrode active material of the negative electrode layer contains an average working potential vs Li / Li +For the first active material and the second active material which are different from each other, in a discharge curve having the discharge amount (capacity / μAh) as the horizontal axis and the cell voltage (V) as the vertical axis, a second flat portion appearing after the first flat portion appearing after the start of discharge and having a lower cell voltage than the first flat portion is detected as the end point.

[0026] In the above-mentioned method for detecting the endpoint voltage of the all-solid-state battery, it can be: when the total current capacity during discharge is assumed to be 100 cap.% (100 capacity percentage), the absolute value of the inclination of the first flat portion and the second flat portion is in the range below 2 mV / cap.% (2 mV per capacity percentage).

[0027] Effects of the Invention

[0028] The present invention can provide an all-solid-state battery that can easily perform endpoint detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a schematic cross-sectional view showing the basic structure of an all-solid-state battery.

[0030] Figure 2 This is a diagram illustrating a discharge curve in the case where the positive electrode contains one type of positive electrode active material.

[0031] Figure 3 is a schematic cross-sectional view of the first internal electrode.

[0032] Figure 4 This is a diagram illustrating a discharge curve of the first internal electrode when the first internal electrode contains the first positive electrode active material and the second positive electrode active material.

[0033] Figure 5 This is a diagram illustrating a discharge curve in the case where the negative electrode contains one type of negative electrode active material.

[0034] Figure 6 is a schematic cross-sectional view of the second internal electrode.

[0035] Figure 7 This is a diagram illustrating a discharge curve of the second internal electrode when the second internal electrode contains the first negative electrode active material and the second negative electrode active material.

[0036] Figure 8 is a schematic cross-sectional view of an all-solid-state battery according to an embodiment.

[0037] Fig. 9 is a schematic cross-sectional view of another all-solid-state battery.

[0038] Fig.10 This is a diagram illustrating the flow of a method for manufacturing an all-solid-state battery.

[0039] Fig.11A and Fig. 11B It is a diagram illustrating a lamination process.

[0040] Description of Reference Numerals

[0041] 10 first internal electrode, 11 first collector layer, 20 second internal electrode, 21 second collector layer, 30 solid electrolyte layer, 40a first external electrode, 40b second external electrode, 50 covering layer, 51 solid electrolyte raw sheet, 52 internal electrode paste, 53 reverse pattern, 54 covering sheet, 55 external electrode paste, 60 stacked sheet, 100, 100a all-solid-state battery. DETAILED DESCRIPTION

[0042] Hereinafter, embodiments will be described with reference to the drawings.

[0043] (First Embodiment)

[0044] Figure 1 is a schematic cross-sectional view showing the basic structure of the all-solid-state battery 100. Figure 1 As shown in the example, the all-solid battery 100 has a structure in which a solid electrolyte layer 30 is sandwiched between a first internal electrode 10 and a second internal electrode 20. The first internal electrode 10 is formed on a first main surface of the solid electrolyte layer 30. The second internal electrode 20 is formed on a second main surface of the solid electrolyte layer 30.

[0045] When the all-solid battery 100 is used as a secondary battery, one of the first internal electrode 10 and the second internal electrode 20 is used as a positive electrode, and the other is used as a negative electrode. In this embodiment, as an example, the first internal electrode 10 is used as a positive electrode, and the second internal electrode 20 is used as a negative electrode.

[0046] The solid electrolyte layer 30 has a solid electrolyte with ion conductivity as a main component. The solid electrolyte of the solid electrolyte layer 30 is, for example, an oxide-based solid electrolyte with lithium ion conductivity. The solid electrolyte is, for example, a phosphate-based solid electrolyte with a NASICON structure. The phosphate-based solid electrolyte with a NASICON structure has high electrical conductivity and is stable in the atmosphere. The phosphate-based solid electrolyte is, for example, a lithium-containing phosphate. The phosphate is not particularly limited, and examples thereof include composite lithium phosphate salts with Ti (e.g., LiTi2(PO4)3). Alternatively, part or all of Ti may be replaced with a tetravalent transition metal such as Ge, Sn, Hf, or Zr. In addition, in order to increase the Li content, part of Ti may be replaced with a trivalent transition metal such as Al, Ga, In, Y, or La. More specifically, for example, Li 1+x Alx Ge 2-x (PO4)3、Li 1+x Al x Zr 2-x (PO4)3、Li 1+x Al x Ti 2-x (PO4)3, etc. For example, it is preferred that a Li-Al-Ge-PO4 type material to which a transition metal is pre-added is the same as the transition metal contained in the phosphate having an olivine-type crystal structure contained in the first internal electrode 10 and the second internal electrode 20. For example, in the case where the first internal electrode 10 and the second internal electrode 20 contain a phosphate containing Co and Li, it is preferred that the solid electrolyte layer 30 contain a Li-Al-Ge-PO4 type material to which Co is pre-added. In this case, the effect of suppressing the dissolution of the transition metal contained in the electrode active material into the electrolyte can be obtained. In the case where the first internal electrode 10 and the second internal electrode 20 contain a phosphate containing a transition metal other than Co and Li, it is preferred that the solid electrolyte layer 30 contain a Li-Al-Ge-PO4 type material to which the transition metal is pre-added.

[0047] The first internal electrode 10 used as the positive electrode contains a substance having an olivine-type crystal structure as an electrode active material. Preferably, the second internal electrode 20 also contains the electrode active material. As such an electrode active material, phosphates containing transition metals and lithium can be cited. The olivine-type crystal structure is a crystal possessed by natural olivine, and can be identified by X-ray diffraction.

[0048] As a typical example of an electrode active material having an olivine-type crystal structure, LiCoPO4 containing Co can be used. Phosphates in which Co of a transition metal is replaced in the chemical formula can also be used. Here, the ratio of Li and PO4 can be changed according to the valence. As transition metals, Co, Mn, Fe, Ni, etc. are preferably used.

[0049] The electrode active material having an olivine-type crystal structure functions as a positive electrode active material in the first internal electrode 10 that functions as a positive electrode. For example, when the electrode active material having an olivine-type crystal structure is contained only in the first internal electrode 10, the electrode active material functions as a positive electrode active material. When the electrode active material having an olivine-type crystal structure is also contained in the second internal electrode 20, in the second internal electrode 20 that functions as a negative electrode, although its mechanism of action is not completely clear, it is possible to exert the effects of increasing the discharge capacity and increasing the working potential accompanying discharge, and it is presumed that these effects are caused by forming a partial solid solution state with the negative electrode active material.

[0050] In the case where both the first internal electrode 10 and the second internal electrode 20 contain an electrode active material having an olivine crystal structure, the respective electrode active materials preferably contain transition metals that may be the same or different from each other. "May be the same or different from each other" means that the electrode active materials contained in the first internal electrode 10 and the second internal electrode 20 may contain the same transition metal or may contain transition metals of different types. The first internal electrode 10 and the second internal electrode 20 may contain only one transition metal or may contain two or more transition metals. Preferably, the first internal electrode 10 and the second internal electrode 20 contain the same transition metal. More preferably, the chemical composition of the electrode active materials contained in the two electrodes is the same. By containing the same transition metal or the same composition of electrode active materials in the first internal electrode 10 and the second internal electrode 20, the similarity of the composition of the two internal electrode layers is improved, and therefore, the following effect is achieved: even if the positive and negative terminals of the all-solid-state battery 100 are installed inverted, it can be actually used without malfunctioning according to the purpose.

[0051] The second internal electrode 20 contains a negative electrode active material. By making only one electrode contain a negative electrode active material, it becomes clear that the one electrode functions as a negative electrode and the other electrode functions as a positive electrode. In addition, both electrodes may contain a substance known as a negative electrode active material. Regarding the negative electrode active material of the electrode, appropriate reference may be made to the prior art of secondary batteries, for example, compounds such as titanium oxide, lithium titanium composite oxide, lithium titanium composite phosphate, carbon, and lithium vanadium phosphate may be cited.

[0052] In the production of the first internal electrode 10 and the second internal electrode 20, in addition to these electrode active materials, solid electrolytes with ion conductivity, conductive materials (conductive aids), etc. can also be added. By uniformly dispersing these materials in water or an organic solvent together with a binder and a plasticizer, a paste for the internal electrode can be obtained. As a conductive aid, a carbon material or the like can be contained. As a conductive aid, a metal can also be contained. Metals as conductive aids include Pd, Ni, Cu, Fe, alloys containing them, etc. The solid electrolyte contained in the first internal electrode 10 and the second internal electrode 20 can be the same as the solid electrolyte as the main component of the solid electrolyte layer 30, for example.

[0053] Here, a case where the first internal electrode 10 contains one type of positive electrode active material is examined. Figure 2 is a diagram illustrating a discharge curve of the first internal electrode 10 in this case. Figure 2 In the figure, the horizontal axis represents the discharge capacity (capacity / μAh) and the vertical axis represents the single cell voltage. Figure 2As shown in the example, even if the discharge is in progress, the cell voltage is roughly constant, and the slope of the cell voltage relative to the discharge amount is small. However, at the end of the discharge when the remaining battery amount decreases, the slope of the cell voltage relative to the discharge amount increases sharply, and the cell voltage drops sharply. In this case, even if charging is started after the end voltage is detected, the cell voltage may drop significantly compared to the end voltage. Therefore, it is difficult to detect the end point.

[0054] Therefore, in the present embodiment, the first internal electrode 10 has an average operating potential vs Li / Li + At least two positive electrode active materials that are different from each other. For example, at least one of the components and composition ratios of the two positive electrode active materials is different. The positive electrode active material with a higher average working potential among the two positive electrode active materials is called the first positive electrode active material, and the positive electrode active material with a lower average working potential among the two positive electrode active materials is called the second positive electrode active material. The average working potential refers to the average single cell voltage when the current capacity from full charge to discharge at 0.05C to 3V is 100% in a half-cell (metal lithium is configured in the counter electrode) obtained using the active material and the electrolyte, and the discharge is 10% to 90%.

[0055] Figure 3 is a schematic cross-sectional view of the first internal electrode 10. Figure 3 As shown in the example, in the first internal electrode 10, the crystal grains of the first positive electrode active material 15 and the crystal grains of the second positive electrode active material 16 are mixed. In fact, the first internal electrode 10 contains a solid electrolyte, a conductive additive, etc., but in Figure 3 Omitted in .

[0056] Figure 4 1 is a diagram illustrating a discharge curve of the first internal electrode 10 when the first internal electrode 10 contains the first positive electrode active material 15 and the second positive electrode active material 16. Figure 4 As shown in the example, after the discharge starts, a first potential flat portion appears in which the decrease (inclination) of the cell voltage relative to the discharge amount is less than a threshold value. The first potential flat portion is generated by the first positive electrode active material. As the discharge proceeds, after the decrease (inclination) of the cell voltage relative to the discharge amount increases, a second potential flat portion appears in which the decrease (inclination) of the cell voltage relative to the discharge amount is less than a threshold value. The second potential flat portion is generated by the second positive electrode active material. After that, as the discharge proceeds, the decrease in the cell voltage increases sharply. Among them, the potential flat portion refers to the range in which the absolute value of the inclination of the discharge curve is below 2mV / cap.% when the total current capacity during discharge is 100cap.%.

[0057] If the second potential flat portion is detected as the end point, the end point detection becomes easy, and charging can be started before the cell voltage drops significantly compared to the end point voltage. Therefore, the necessary cell voltage can be ensured.

[0058] When the difference between the average working potential (first average working potential) of the first positive electrode active material 15 and the average working potential (second average working potential) of the second positive electrode active material 16 is small, it is possible that the detection of the second average working potential becomes difficult. Therefore, it is preferred to set a lower limit for the difference between the first average working potential and the second average working potential. For example, the difference between the first average working potential and the second average working potential is preferably greater than 0.2V, more preferably greater than 0.25V, and further preferably greater than 0.3V. On the other hand, when the difference between the first average working potential and the second average working potential is large, the single cell voltage may become smaller depending on the negative electrode active material contained in the second internal electrode 20. Therefore, it is preferred to set an upper limit for the difference between the first average working potential and the second average working potential. For example, the difference between the first average working potential and the second average working potential is preferably less than 1.5V, more preferably less than 1.0V, and further preferably less than 0.5V.

[0059] For example, LiCoPO4 or the like can be used as the first positive electrode active material 15, and Li6Co5(P2O7)4 or the like can be used as the second positive electrode active material 16. In this case, LiCoPO4 has an average voltage of 4.9 V vs Li / Li. + The average working potential of Li6Co5(P2O7)4 is 0.3V to 0.5V lower than the average working potential. Therefore, a high cell voltage can be easily obtained, and the difference in the average working potential becomes large, making it easy to detect the end point.

[0060] When the average crystal particle size of the second positive electrode active material 16 is too small, a mutual diffusion reaction may occur between the two active materials. When the average crystal particle size of the second positive electrode active material 16 is too large, undesirable conditions such as a decrease in the working rate of the active material and deterioration of the rate characteristics may occur. Therefore, it is preferred to set a lower limit and an upper limit for the average crystal particle size of the second positive electrode active material 16. For example, the average crystal particle size of the second positive electrode active material 16 is preferably 0.5 μm or more and 50 μm or less, more preferably 1.0 μm or more and 30 μm or less, and further preferably 1.5 μm or more and 20 μm or less.

[0061] When the average crystal particle size of the first positive electrode active material 15 is too small, a mutual diffusion reaction may occur between the two active materials. When the average crystal particle size of the first positive electrode active material 15 is too large, adverse conditions such as a decrease in the working rate of the active material and deterioration of the rate characteristics may occur. Therefore, it is preferred to set a lower limit and an upper limit for the average crystal particle size of the first positive electrode active material 15. For example, the average crystal particle size of the first positive electrode active material 15 is preferably 0.5 μm to 50 μm, more preferably 1.0 μm to 30 μm, and further preferably 1.5 μm to 20 μm.

[0062] When the amount of the first positive electrode active material 15 is too much, endpoint detection may become difficult. Therefore, it is preferable to set an upper limit on the amount of the first positive electrode active material 15. On the other hand, when the amount of the second positive electrode active material 16 is too much, the energy density may decrease. Therefore, it is preferable to set a lower limit on the amount of the second positive electrode active material 16. For example, in the cross section of the first internal electrode 10, the ratio of the area of ​​the first positive electrode active material 15 to the total area of ​​the first positive electrode active material 15 and the second positive electrode active material 16 is 85% or more, 90% or more, or 95% or more. In addition, in the cross section of the first internal electrode 10, the ratio of the area of ​​the second positive electrode active material 16 to the total area of ​​the first positive electrode active material 15 and the second positive electrode active material 16 is 5% or more, 10% or more, or 15% or more.

[0063] The first internal electrode 10 preferably further contains Li2CoP2O7. In this case, mutual reaction during firing can be suppressed, the battery reaction of Li6Co5(P2O7)4 becomes uniform, and a flat potential can be clearly detected.

[0064] (Second Embodiment)

[0065] Here, a case where the second internal electrode 20 contains one type of negative electrode active material is examined. Figure 5 2 is a diagram illustrating a discharge curve of the second internal electrode 20 in this case. Figure 5 In the figure, the horizontal axis represents the discharge capacity (capacity / μAh) and the vertical axis represents the single cell voltage. Figure 5 As shown in the example, even if the discharge is in progress, the cell voltage is roughly constant, and the slope of the cell voltage relative to the discharge amount is small. However, at the end of the discharge when the remaining battery amount decreases, the slope of the cell voltage relative to the discharge amount increases sharply, and the cell voltage drops sharply. In this case, even if charging is started after the end voltage is detected, the cell voltage may drop significantly compared to the end voltage. Therefore, it is difficult to detect the end point.

[0066] Therefore, in the present embodiment, the second inner electrode 20 has an average operating potential vs Li / Li+ At least two negative electrode active materials that are different from each other. For example, at least one of the components and composition ratios of the two negative electrode active materials is different. The negative electrode active material with a lower average working potential among the two negative electrode active materials is referred to as the first negative electrode active material, and the negative electrode active material with a higher average working potential among the two negative electrode active materials is referred to as the second negative electrode active material. The average working potential refers to the average single cell voltage when the current capacity from full charge to discharge (Li separation) to 3V at 0.05C is 100% in a half-cell (metal lithium is configured in the counter electrode) obtained using the active material and the electrolyte, and the discharge is 10% to 90%.

[0067] Figure 6 2 is a schematic cross-sectional view of the second internal electrode 20. Figure 2 As shown in the example, in the second internal electrode 20, the crystal grains of the first negative electrode active material 25 and the crystal grains of the second negative electrode active material 26 are mixed. In addition, in fact, the second internal electrode 20 contains a solid electrolyte, a conductive additive, etc., but in Figure 6 Omitted in .

[0068] Figure 7 2 is a diagram illustrating a discharge curve of the second internal electrode 20 when the second internal electrode 20 contains the first negative electrode active material 25 and the second negative electrode active material 26. Figure 7 As shown in the example, after the discharge starts, a first potential flat portion appears in which the decrease (inclination) of the cell voltage relative to the discharge amount is less than a threshold value. The first potential flat portion is generated by the first negative electrode active material. As the discharge proceeds, after the decrease (inclination) of the cell voltage relative to the discharge amount increases, a second potential flat portion appears in which the decrease (inclination) of the cell voltage relative to the discharge amount is less than a threshold value. The second potential flat portion is generated by the second negative electrode active material. After that, as the discharge proceeds, the decrease in the cell voltage increases sharply. Among them, the potential flat portion refers to a range in which the absolute value of the inclination of the discharge curve is less than 2mV / cap.% when the total current capacity during discharge is 100cap.%.

[0069] If the second potential flat portion is detected as the end point, the end point detection becomes easy, and charging can be started before the cell voltage drops significantly compared to the end point voltage. Therefore, the necessary cell voltage can be ensured.

[0070] For example, when the difference between the average working potential (first average working potential) of the first negative electrode active material 25 and the average working potential (second average working potential) of the second negative electrode active material 26 is small, it is possible that the detection of the second average working potential becomes difficult. Therefore, it is preferred to set an upper limit for the average working potential of the first negative electrode active material 25 and a lower limit for the average working potential of the second negative electrode active material 26. For example, the first average working potential is preferably below 1.9V, more preferably below 1.8V, and further preferably below 1.7V. The average working potential of the second negative electrode active material is preferably above 2.2V, more preferably above 2.3V, and further preferably above 2.4V. If the difference between the average working potential of the first negative electrode active material 25 and the average working potential of the second negative electrode active material 26 is too small, detection becomes difficult, and therefore, it is preferably above 0.3V, more preferably above 0.5V, and further preferably above 0.7V.

[0071] For example, the first negative electrode active material 25 may be TiO2, Li 1-2x M x TiOPO4 (M is a divalent metal element, 0≤x≤0.5), Li 3x La 2 / 3-x Any one of TiO3, Nb2O5 and Nb-Ti-O based compounds.

[0072] For example, the second negative electrode active material 26 may be a Ti-containing phosphate or TiP2O7 having a NASICON crystal structure. The Ti-containing phosphate may be Li 1+y A y Ti 2-y (PO4)3 (A is a trivalent metal element, 0≤y≤0.7).

[0073] When the average crystal particle size of the second negative electrode active material 26 is too small, mutual diffusion reaction may occur between materials during firing. When the average crystal particle size of the second negative electrode active material 26 is too large, the working rate of the active material may decrease, the rate characteristics may deteriorate, etc. Therefore, it is preferred to set a lower limit and an upper limit for the average crystal particle size of the second negative electrode active material 26. For example, the average crystal particle size of the second negative electrode active material 26 is preferably 0.5 μm or more and 50 μm or less, more preferably 1.0 μm or more and 30 μm or less, and further preferably 1.5 μm or more and 20 μm or less.

[0074] When the average crystal particle size of the first negative electrode active material 25 is too small, mutual diffusion reaction may occur between materials during firing. When the average crystal particle size of the first negative electrode active material 25 is too large, the working rate of the active material may decrease, the rate characteristics may deteriorate, etc. Therefore, it is preferred to set a lower limit and an upper limit for the average crystal particle size of the first negative electrode active material 25. For example, the average crystal particle size of the first negative electrode active material 25 is preferably 0.5 μm or more and 50 μm or less, more preferably 1.0 μm or more and 30 μm or less, and further preferably 1.5 μm or more and 20 μm or less.

[0075] When the amount of the first negative electrode active material 25 is too much, endpoint detection may become difficult. Therefore, it is preferable to set an upper limit on the amount of the first negative electrode active material 25. On the other hand, when the amount of the second negative electrode active material 26 is too much, the energy density may decrease. Therefore, it is preferable to set a lower limit on the amount of the second negative electrode active material 26. For example, in the cross section of the second internal electrode 20, the ratio of the area of ​​the first negative electrode active material 25 to the total area of ​​the first negative electrode active material 25 and the second negative electrode active material 26 is 85% or more, 90% or more, or 95% or more. In addition, in the cross section of the second internal electrode 20, the ratio of the area of ​​the second negative electrode active material 26 to the total area of ​​the first negative electrode active material 25 and the second negative electrode active material 26 is 5% or more, 10% or more, or 15% or more.

[0076] Figure 8 It is a schematic cross-sectional view of a stacked all-solid battery 100a having a plurality of battery cells stacked thereon. The all-solid battery 100a includes a stack sheet 60 having a substantially rectangular shape. A first external electrode 40a and a second external electrode 40b are provided in a manner in contact with two of the four surfaces other than the upper surface and the lower surface at both ends of the stacking direction of the stack sheet 60, i.e., two side surfaces. The two side surfaces may be two adjacent side surfaces or two side surfaces opposite to each other. In the present embodiment, the first external electrode 40a and the second external electrode 40b are provided in a manner in contact with two side surfaces opposite to each other (hereinafter referred to as two end surfaces).

[0077] In the following description, components having the same composition range, the same thickness range, and the same particle size distribution range as those of the all-solid-state battery 100 are denoted by the same reference numerals, and detailed description thereof is omitted.

[0078] In the all-solid battery 100a, a plurality of first internal electrodes 10 and a plurality of second internal electrodes 20 are alternately stacked via a solid electrolyte layer 30. The end edges of the plurality of first internal electrodes 10 are exposed at the first end face of the laminate sheet 60, but not at the second end face of the laminate sheet 60. The end edges of the plurality of second internal electrodes 20 are exposed at the second end face of the laminate sheet 60, but not at the first end face of the laminate sheet 60. Thus, the first internal electrodes 10 and the second internal electrodes 20 are alternately connected to the first external electrode 40a and the second external electrode 40b. The solid electrolyte layer 30 extends from the first external electrode 40a to the second external electrode 40b. As described above, the all-solid battery 100a has a structure in which a plurality of battery cells are stacked.

[0079] On the upper surface (at the Figure 8 In the example of FIG. 1 , the cover layer 50 is stacked on the upper surface of the first internal electrode 10 of the uppermost layer. Figure 8 In the example of the embodiment, the lower surface of the first internal electrode 10 of the lowest layer is also stacked with a covering layer 50. The covering layer 50 is mainly composed of an inorganic material (such as Al2O3, ZrO2, TiO2, etc.) containing Al, Zr, Ti, etc. Alternatively, the covering layer 50 may contain the main component of the solid electrolyte layer 30 as a main component.

[0080] The first internal electrode 10 and the second internal electrode 20 may include a current collector layer. Fig. 9 As shown in the example, the first collector layer 11 is provided in the first internal electrode 10. In addition, the second collector layer 21 can be provided in the second internal electrode 20. The first collector layer 11 and the second collector layer 21 have a conductive material as a main component. For example, metal, carbon, etc. can be used as the conductive material of the first collector layer 11 and the second collector layer 21. By connecting the first collector layer 11 to the first external electrode 40a and connecting the second collector layer 21 to the second external electrode 40b, the current collection efficiency is improved.

[0081] Next, Figure 8 A method for manufacturing the all-solid-state battery 100a exemplified in FIG. 1 is described. Fig.10 It is a diagram illustrating the flow of a method for manufacturing the all-solid-state battery 100 a.

[0082] (Step of preparing raw material powder for solid electrolyte layer)

[0083] First, a raw material powder for a solid electrolyte layer constituting the above-mentioned solid electrolyte layer 30 is prepared. For example, the raw materials, additives, etc. can be mixed and the raw material powder for the solid electrolyte layer can be prepared by using a solid phase synthesis method or the like. The obtained raw material powder can be adjusted to a desired average crystal particle size by dry grinding. For example, the desired average crystal particle size can be adjusted by using a planetary ball mill using a 5 mm φ ZrO2 ball.

[0084] (Process for producing raw material powder for covering layer)

[0085] First, a raw material powder of the ceramic constituting the above-mentioned covering layer 50 is prepared. For example, the raw material, additives, etc. can be mixed and the raw material powder for the covering layer can be prepared by using a solid phase synthesis method or the like. The obtained raw material powder can be adjusted to a desired average crystal particle size by dry grinding. For example, the desired average crystal particle size can be adjusted by using a planetary ball mill using a 5 mm φ ZrO2 ball.

[0086] (Internal electrode paste production process)

[0087] Next, prepare the internal electrode paste for preparing the above-mentioned first internal electrode 10 and second internal electrode 20. For example, the internal electrode paste can be obtained by uniformly dispersing a conductive aid, an electrode active material, a solid electrolyte material, a sintering aid, a binder, a plasticizer, etc. in water or an organic solvent. As a solid electrolyte material, the above-mentioned solid electrolyte paste can be used. As a conductive aid, a carbon material or the like is used. As a conductive aid, a metal can also be used. Metals as conductive aids include Pd, Ni, Cu, Fe, alloys containing them, etc. Pd, Ni, Cu, Fe, alloys containing them, various carbon materials, etc. can be further used. In the case where the compositions of the first internal electrode 10 and the second internal electrode 20 are different, it is sufficient to prepare their respective internal electrode pastes.

[0088] As a sintering aid for the internal electrode paste, for example, it can contain any one or more glass components such as Li-BO compounds, Li-Si-O compounds, Li-CO compounds, Li-SO compounds, and Li-PO compounds.

[0089] (External electrode paste production process)

[0090] Next, an external electrode paste for forming the first external electrode 40a and the second external electrode 40b is prepared. For example, the external electrode paste can be obtained by uniformly dispersing a conductive material, glass frit, a binder, a plasticizer, etc. in water or an organic solvent.

[0091] (Solid Electrolyte Green Sheet Production Process)

[0092] The raw material powder for the solid electrolyte layer is uniformly dispersed in an aqueous solvent or an organic solvent together with a binding material, a dispersant, a plasticizer, etc., and wet-pulverized to obtain a solid electrolyte slurry having a desired average crystal particle size. At this time, a bead mill, a wet jet mill, various mixers, a high-pressure homogenizer, etc. can be used. From the viewpoint of being able to simultaneously adjust and disperse the particle size distribution, a bead mill is preferably used. A binder is added to the obtained solid electrolyte slurry to obtain a solid electrolyte paste. By applying the obtained solid electrolyte paste, a solid electrolyte raw sheet 51 can be prepared. The coating method is not particularly limited, and a slit coating method, a reverse coating method, a gravure coating method, a strip coating method, a blade coating method, etc. can be used. The particle size distribution after wet pulverization can be measured, for example, using a laser diffraction measuring device using a laser diffraction scattering method.

[0093] (Lamination process)

[0094] like Fig.11A As shown in the example, internal electrode paste 52 is printed on one side of solid electrolyte green sheet 51. The thickness of internal electrode paste 52 is greater than the thickness of solid electrolyte green sheet 51. In the area of ​​solid electrolyte green sheet 51 where internal electrode paste 52 is not printed, reverse pattern 53 is printed. As reverse pattern 53, the same material as solid electrolyte green sheet 51 can be used. Multiple solid electrolyte green sheets 51 after printing are alternately stacked. Fig. 11B As shown in the example, the cover sheet 54 is pressed from the top and bottom of the stacking direction to obtain a laminate. In this case, a laminate having a substantially rectangular parallelepiped shape is obtained in which the internal electrode paste 52 is alternately exposed on two end faces in the laminate. The cover sheet 54 can be formed by applying the raw material powder for the cover layer in the same manner as the solid electrolyte green sheet production process. The cover sheet 54 is formed thicker than the solid electrolyte green sheet 51. It can be formed thicker during coating or by overlapping a plurality of coated sheets.

[0095] Next, the external electrode paste 55 is applied to each of the two end surfaces by dipping or the like and then dried. Thus, a molded body for forming the all-solid-state battery 100a is obtained.

[0096] (Firing process)

[0097] Next, the obtained laminate is fired. The firing conditions are not particularly limited, and may be listed as being in an oxidizing atmosphere or a non-oxidizing atmosphere, with the maximum temperature preferably being 400°C to 1000°C, more preferably 500°C to 900°C, etc. In order to fully remove the binder before reaching the maximum temperature, a process may be provided in which the temperature is maintained at a temperature lower than the maximum temperature in an oxidizing atmosphere. In order to reduce process costs, it is preferred to fire at as low a temperature as possible. Reoxidation treatment may be performed after firing. Through the above process, an all-solid-state battery 100a is generated.

[0098] Furthermore, the current collector layer can be formed in the first internal electrode 10 and the second internal electrode 20 by laminating the internal electrode paste, the current collector paste containing a conductive material, and the internal electrode paste in this order.

[0099] [Example]

[0100] Next, an all-solid-state battery was produced according to the embodiment and its characteristics were investigated.

[0101] (Example 1)

[0102] The positive electrode active materials are LiCoPO4 and Li6Co5(P2O7)4. The conductive auxiliary agent acetylene black and the solid electrolyte LAGP (Li-Al-Ge-PO4 type) are further added, ground and mixed in a weight ratio of 50:5:10:35, and stirred with a binder, a dispersant, and an organic solvent to make a positive electrode paste. The positive electrode layer is formed by applying the positive electrode paste on the LAGP sintered body particles of Φ15mm prepared separately, and the electrode layer is sintered at 650℃ in an inactive atmosphere. After that, the Au collector is formed on the positive electrode coating surface by sputtering, and the metal Li is configured on the counter electrode in an argon atmosphere glove box through a polymer electrolyte membrane composed of polyethylene oxide and LiTFSI (lithium bis(trifluoromethane)sulfonyl imide), and sealed in a 2032-type button battery to make a positive electrode half-cell.

[0103] (Example 2)

[0104] The positive electrode active materials were LiCoPO4, Li6Co5(P2O7)4 and Li2CoP2O7, and acetylene black and LAGP were further added in a weight ratio of 45:5:5:10:35. A positive electrode half-cell was prepared in the same manner as in Example 1. As in Example 1, two potential flat portions were observed during both charging and discharging, but the potential flat portion of the second portion was flatter and was judged to be more suitable for endpoint detection.

[0105] (Comparative Example 1)

[0106] A positive electrode half-cell was prepared in the same manner as in Example 1 except that the positive electrode active material was only LiCoPO4 and acetylene black and LAGP were further added in a weight ratio of 50:10:35.

[0107] (Comparative Example 2)

[0108] A positive electrode half-cell was prepared in the same manner as in Comparative Example 1, except that the positive electrode active material was Li6Co5(P2O7)4.

[0109] (Comparative Example 3)

[0110] The positive electrode half-cell was prepared in the same manner as in Example 1 except that the positive electrode constituent materials were Li2CoP2O7, conductive aid acetylene black and solid electrolyte LAGP in a weight ratio of 50:5:10:35.

[0111] (analyze)

[0112] The half-cells of Examples 1 and 2 and Comparative Examples 1 to 3 were subjected to constant current charge and discharge measurements in a constant temperature chamber at 80°C in the range of 3.0V to 5.2V. The results are shown in Table 1. In Example 1, two potential flat portions were observed in both charge and discharge. In discharge, at the end of discharge, the potential flat portion was 4.6V vs Li / Li + Nearby, a potential flat portion is observed with a capacity of about 1 / 10 of the whole, which is judged to be suitable for endpoint detection. In Example 2, two segments of potential flat portions are observed in both charging and discharging as in Example 1, but the potential flat portion of the second segment is flatter and is judged to be more suitable for endpoint detection. From these results, it can be seen that by making the positive electrode contain two kinds of positive electrode active materials with different average working potentials, two segments of potential flat portions appear clearly. It can also be seen that by making the positive electrode further contain Li2CoP2O7, the potential flat portion of the second segment can be clearly detected.

[0113] In Comparative Example 1, two potential flat sections were observed around 4.8V to 5.0V in both charge and discharge, but because the voltage difference was small and a step difference appeared at about half of the capacity, it was judged that the second section of the discharge curve was not suitable for endpoint detection. In Comparative Example 2, one potential flat section was observed around 4.6V in both charge and discharge, but the voltage dropped sharply at the end of discharge, so it was judged that endpoint detection was difficult. In Comparative Example 3, one potential flat section was observed around 4.9V in both charge and discharge, but the voltage dropped sharply at the end of discharge, so it was judged that endpoint detection was difficult.

[0114] [Table 1]

[0115]

[0116] (Example 3)

[0117] The negative electrode active materials are TiO2 and LiTi2(PO4)3. Acetylene black and solid electrolyte LAGP (Li-Al-Ge-PO4) are further added as conductive additives. They are ground and mixed in a weight ratio of 50:5:10:35, and stirred with a binder, a dispersant, and an organic solvent to make a negative electrode paste. The negative electrode layer is formed by applying the negative electrode paste on the LAGP sintered body particles of Φ15mm prepared separately, and the electrode layer is sintered at 600°C in an inactive atmosphere. After that, an Au collector is formed on the negative electrode coating surface by sputtering.

[0118] LiCoPO4 as a positive electrode active material, acetylene black as a conductive aid, and solid electrolyte LAGP are added, ground and mixed in a weight ratio of 55:10:35, and stirred with a binder, a dispersant, and an organic solvent to make a positive electrode paste. The positive electrode layer is formed by applying the positive electrode paste on the LAGP sintered body particles of Φ15mm prepared separately, and the electrode layer is sintered at 600°C in an inactive atmosphere. After that, an Au collector is formed on the negative electrode coating surface by sputtering. At this time, the coating amount of the positive electrode layer is adjusted so that the theoretical capacity calculated by the mass of the positive electrode active material becomes 1.3 times the theoretical capacity calculated by the total amount of the negative electrode active material.

[0119] Afterwards, in an argon atmosphere glove box, the positive electrode layer and the negative electrode layer were arranged with a polymer electrolyte membrane composed of polyethylene oxide and LiTFSI (lithium bis(trifluoromethane)sulfonyl imide) interposed therebetween and sealed in a 2032-type button cell to produce an all-solid-state battery.

[0120] (Example 4)

[0121] The all-solid-state battery was prepared in the same manner as in Example 3 using two types of negative electrode active materials: LiTiOPO4 and LiTi2(PO4)3.

[0122] (Example 5)

[0123] The negative electrode active material is TiO2 and Li 1.3 Al 0.3 Ti 1.7 A fully solid-state battery was prepared in the same manner as in Example 3 using these two types of (PO4)3.

[0124] (Example 6)

[0125] The negative electrode active material is LiTiOPO4 and Li 1.3 Al 0.3 Ti 1.7 A fully solid-state battery was prepared in the same manner as in Example 3 using these two types of (PO4)3.

[0126] (Example 7)

[0127] The negative electrode active material is Li 0.33 La 0.55 A fully solid-state battery was prepared using TiO3 and LiTi2(PO4)3 in the same manner as in Example 3.

[0128] (Example 8)

[0129] The negative electrode active material is Li 0.33 La 0.55 TiO3 and Li 1.3 Al 0.3 Ti 1.7 A fully solid-state battery was prepared in the same manner as in Example 3 using these two types of (PO4)3.

[0130] (Comparative Example 4)

[0131] An all-solid-state battery was produced in the same manner as in Example 3 except that TiO 2 was used as the negative electrode active material alone and acetylene black and LAGP were further added in a weight ratio of 50:10:35.

[0132] (Comparative Example 5)

[0133] An all-solid-state battery was prepared in the same manner as in Comparative Example 4 except that LiTiOPO4 was used as the negative electrode active material.

[0134] (Comparative Example 6)

[0135] In addition to making the negative electrode active material Li 0.33 La 0.55 A fully solid-state battery was produced in the same manner as in Comparative Example 4 except for TiO3.

[0136] (analyze)

[0137] The all-solid batteries of Examples 3 to 8 and Comparative Examples 4 to 6 were subjected to constant current charge and discharge measurements in a constant temperature chamber at 80°C in the range of 1.0V to 3.7V. The results are shown in Table 2. In Example 3, two potential flat sections were observed in both charge and discharge. In discharge, at the end of discharge, the potential flat section was 2.4V vs Li / Li + In Example 4, two potential flat sections were observed in both charge and discharge as in Example 3. In the discharge, the potential flat section was observed at 2.4 V vs Li / Li at the end of the discharge. +In Example 5, two potential flat sections were observed in both charge and discharge as in Example 3. In the discharge, the potential flat section was observed at 2.4 V vs Li / Li at the end of the discharge. + In Example 6, two potential flat sections were observed in both charge and discharge as in Example 3. In the discharge, the potential flat section was observed at 2.4 V vs Li / Li at the end of the discharge. + In Example 7, two potential flat sections were observed in both charge and discharge as in Example 3. In the discharge, the potential flat section was observed at 2.4 V vsLi / Li at the end of the discharge. + In Example 8, two potential flat sections were observed in both charge and discharge as in Example 3. In the discharge, the potential flat section was observed at 2.4 V vs Li / Li at the end of the discharge. + Near the 2000A, a potential flat portion was observed at about 1 / 10 of the total capacity, which was judged to be suitable for endpoint detection. From these results, it can be seen that by making the negative electrode contain two negative electrode active materials with different average working potentials, two stages of potential flat portions clearly appear.

[0138] In Comparative Example 4, a potential flat section was observed at around 3.0 V in both charge and discharge, but the voltage dropped sharply at the end of discharge, so it was judged that it was difficult to detect the end point. In Comparative Example 5, a potential flat section was observed at around 3.3 V in both charge and discharge, but the voltage dropped sharply at the end of discharge, so it was judged that it was difficult to detect the end point. In Comparative Example 6, a potential flat section was observed at around 3.1 V in both charge and discharge, but the voltage dropped sharply at the end of discharge, so it was judged that it was difficult to detect the end point.

[0139] [Table 2]

[0140]

[0141] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to these specific embodiments, and various modifications and changes can be made within the scope of the gist of the present invention described in the claims.

Claims

1. An all-solid-state battery, characterized in that: include: Oxide solid electrolyte layer; a positive electrode layer formed on the first main surface of the oxide-based solid electrolyte layer, the positive electrode layer containing a positive electrode active material; and a negative electrode layer formed on the second main surface of the oxide-based solid electrolyte layer, the negative electrode layer containing a negative electrode active material, The positive electrode active material contains a first positive electrode active material and a second positive electrode active material. Average working potential of the first positive electrode active material vs Li / Li + Higher than the average working potential of the second positive electrode active material vs Li / Li + , In a cross section of the positive electrode layer, a ratio of an area of ​​the first positive electrode active material to a total area of ​​the first positive electrode active material and the second positive electrode active material is 85% or more, In a cross section of the positive electrode layer, a ratio of an area of ​​the second positive electrode active material to a total area of ​​the first positive electrode active material and the second positive electrode active material is 5% or more, The first positive electrode active material is LiCoPO4, The second positive electrode active material is Li6Co5(P2O7)4, In the positive electrode layer, a weight ratio of the first positive electrode active material is 9 times or more and 10 times or less of a weight ratio of the second positive electrode active material.

2. The all-solid-state battery according to claim 1, characterized in that: Average working potential of the first positive electrode active material vs Li / Li + Average working potential of the second positive electrode active material vs Li / Li + The difference is between 0.2V and 1.5V.

3. The all-solid-state battery according to claim 1 or 2, characterized in that: The second positive electrode active material has an average crystal particle size of 0.5 μm or more and 50 μm or less.

4. The all-solid-state battery according to claim 1 or 2, characterized in that: The positive electrode layer contains Li2CoP2O7.

5. The all-solid-state battery according to claim 1 or 2, characterized in that: The negative electrode layer has an average working potential vs Li / Li + a first negative electrode active material and a second negative electrode active material that are different from each other, Average working potential of the first negative electrode active material vs Li / Li + Below 1.9V, Average working potential of the second negative electrode active material vs Li / Li + Above 2.2V.

6. The all-solid-state battery according to claim 5, characterized in that: The first negative electrode active material is TiO2, Li 1-2x M x TiOPO4、Li 3x La 2 / 3-x Any one of TiO3 and Nb2O5, wherein M is a divalent metal element, and 0≤x≤0.

5.

7. The all-solid-state battery according to claim 5, characterized in that: The second negative electrode active material is a Ti-containing phosphate or TiP2O7 having a NASICON type crystal structure.

8. The all-solid-state battery according to claim 7, characterized in that: The Ti-containing phosphate is Li 1+y A y Ti 2-y (PO4)3, wherein A is a trivalent metal element, 0≤y≤0.

7.

9. The all-solid-state battery according to claim 8, characterized in that: The second negative electrode active material has an average crystal particle size of 0.5 μm or more and 50 μm or less.

10. A method for detecting the endpoint voltage of an all-solid-state battery, characterized in that: The all-solid-state battery comprises: an oxide solid electrolyte layer; a positive electrode layer formed on a first main surface of the oxide solid electrolyte layer, which contains a positive electrode active material; and a negative electrode layer formed on a second main surface of the oxide solid electrolyte layer, which contains a negative electrode active material, wherein at least one of the positive electrode active material of the positive electrode layer and the negative electrode active material of the negative electrode layer contains an average working potential vs Li / Li + a first active substance and a second active substance that are different from each other, In a discharge curve with the discharge amount as the horizontal axis and the single cell voltage as the vertical axis, a second flat portion appearing after the first flat portion appearing after the start of discharge and having a lower single cell voltage than the first flat portion is detected as the end point, wherein the unit of the discharge amount, i.e., capacity, is μAh, and the unit of the single cell voltage is V.

11. The method for detecting the endpoint voltage of an all-solid-state battery according to claim 10, wherein: When the total current capacity during discharge is assumed to be 100 cap.%, the absolute values ​​of the inclinations of the first flat portion and the second flat portion are within a range of 2 mV / cap.% or less.